Properties of novel beta-lactamase produced by Bacteroides fragilis. - Yotsuji, A (1983)
Bacteroides fragilis strains were isolated from clinical specimens. B. fragilis G-237 was highly resistant to beta-lactam antibiotics due to beta-lactamase production. The purified enzyme from this strain gave a single protein band on polyacrylamide gel electrophoresis. The isoelectric point was 4.8, and the molecular weight was estimated to be 26,000 by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The enzyme activity was inhibited by p-chloromercuribenzoate and iodine but not by clavulanic acid or sulbactam. The purified enzyme showed a unique substrate profile by hydrolyzing at a high rate most of the cephalosporins, including cephamycin derivatives, penicillins, and imipenem (formerly imipemide, N-formimidoyl thienamycin, or MK 0787).